Laser in Glaucoma and Ocular Hypertension (LiGHT) trial. A multicentre, randomised controlled trial: design and methodology. Issue 5 (13th September 2017) - Gazzard, Gus; Konstantakopoulou, Evgenia; Garway-Heath, David; Barton, Keith; Wormald, Richard; Morris, Stephen; Hunter, Rachael; Rubin, Gary; Buszewicz, Marta; Ambler, Gareth; Bunce, Catey
Abstract : Purpose: The Laser in Glaucoma and Ocular Hypertension (LiGHT) Trial aims to establish whether initial treatment with selective laser trabeculoplasty (SLT) is superior to initial treatment with topical medication for primary open-angle glaucoma (POAG) or ocular hypertension (OHT). Design: The LiGHT Trial is a prospective, unmasked, multicentre, pragmatic, randomised controlled trial. 718 previously untreated patients with POAG or OHT were recruited at six collaborating centres in the UK between 2012 and 2014. The trial comprises two treatment arms: initial SLT followed by conventional medical therapy as required, and medical therapy without laser therapy. Randomisation was provided online by a web-based randomisation service. Participants will be monitored for 3 years, according to routine clinical practice. The target intraocular pressure (IOP) was set at baseline according to an algorithm, based on disease severity and lifetime risk of loss of vision at recruitment, and subsequently adjusted on the basis of IOP control, optic disc and visual field. The primary outcome measure is health-related quality of life (HRQL) (EQ-5D five-level). Secondary outcomes are treatment pathway cost and cost-effectiveness, Glaucoma Utility Index, Glaucoma Symptom Scale, Glaucoma Quality of Life, objective measures of pathway effectiveness, visual function and safety profiles and concordance. A single main analysis will be performed at the end of the trial on an intention-to-treat basis. Conclusions: The LiGHT Trial is a multicentre, pragmatic, randomised clinical trial that will provide valuable data on the relative HRQL, clinical effectiveness and cost-effectiveness of SLT and topical IOP-lowering medication. Trial registration number: ISRCTN32038223, Pre-results.